Jumping for Joy: The Importance of the Body and of Dynamics in the Expression and Recognition of Positive Emotions - Mortillaro, Marcello; Dukes, Daniel (Frontiers in Psychology, 2018)
For decades now, most research on emotion expression has focused on the static facial prototypes of a few selected, mostly negative emotions. Implicitly, most researchers considered all positive emotions as sharing one common signal, the smile, and consequently as being largely indistinguishable from each other in terms of expression. Recently, a new wave of studies has begun challenging the traditional assumption, considering the role of multiple modalities and of the dynamics in the expression and recognition of positive emotions. Based on these recent studies, we suggest that positive emotions are better expressed and correctly perceived when they are simultaneously communicated through the face and the body and when the perceiver has access to dynamic stimuli. Notably, we argue that this improvement is comparatively more important for positive emotions than for negative emotions. Our view is that the misperception of positive emotions has less immediate and potentially threatening consequences than the misperception of negative emotions; therefore, from an evolutionary perspective, there was only limited benefit in the development of clear, quick signals that allow fine distinctions between them. Consequently, we suggest that the successful communication of positive emotions requires a stronger signal than that of negative emotions and that this signal is provided by the use of the body and the way those movements unfold. We hope our contribution to this growing field provides direction and a theoretical grounding for the many lines of empirical research in the expression and recognition of positive emotion.